The potential of regenerative agriculture in creating climate adaptive and gender inclusive food systems: a study of rural communities in Mpumalanga, South Africa - Govender, Yashila (University of the Witwatersrand, Johannesburg, 2024)
Numerous social-ecological risks to food systems are brought on by industrial agriculture – resulting in various narratives around the sustainability of agriculture, offering a solution to the problems confronting this system. One of these narratives is regenerative agriculture (RA), which has recently gained popularity. The potential of regenerative agriculture could contribute to sustainable agriculture and is capable of addressing climate adaptation challenges and potentially fostering gender inclusivity within food systems. Despite growing interest around regenerative agriculture, this concept is not well understood or researched in South Africa, especially in rural farming villages. This research delves into the multifaceted domain of regenerative agriculture and looks to describe this in the South African context. This study sets out to achieve three research questions, what is the definition of regenerative agriculture in a South African context, what is the current understanding around this concept among smallholder farmers in farming villages of Bushbuckridge and if so, how does regenerative agriculture considers the local gender dynamics in rural farming communities? A mixed methods approach was used for this study. Ten expert interviews with key stakeholders in the agricultural sector were conducted to construct a definition of regenerative agriculture tailored to South African conditions. Thereafter, individual interviews were used to gauge the level of understanding and adoption of regenerative practices among smallholder farmers in the villages of Bushbuckridge. This sample consisted of 74.2% female and 25.8% male. Finally, an in-depth analysis of how regenerative agriculture compared with local dynamics in rural farming communities was conducted through participatory engagement. A total of 54 participants participated in focus group discussions. The results indicate there is a multifaceted understanding of regenerative agriculture in South Africa, with most experts indicating that regenerative agriculture is practiced under the name of conservation agriculture (CA). Aspects of both practices have some commonalities with agroecology, such as principles of soil conservation, polyculture and no-tillage that are highly promoted in South Africa. Additionally, smallholder farmers in Mpumalanga practice regenerative agriculture, with different adoption rates in different villages. Furthermore, this research highlights that the adoption of regenerative agriculture in rural farming communities requires further discussion and stakeholder engagement, especially with women, and includes socio-economic and cultural factors. This study contributes to the broader discourse on regenerative agriculture by providing a context-specific definition, indicating that regenerative agriculture is an overlap of agroecology and conservation agriculture in South Africa, shedding light on the challenges and opportunities for smallholder adoption, and emphasizing the importance of community-based approaches in regenerative agriculture educational programs. The research underscores the need for tailored education and extension programs that account for local conditions and socio-cultural factors.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science, to the Faculty of Science, School of Animal, Plant and Environmental Sciences (APES), University of the Witwatersrand, Johannesburg, 2024.
Keywords: Regenerative Agriculture; Climate Adaptation; Smallholder Farmers; Mpumalanga; UCTD; SDG-13: Climate action; SDG-5: Gender equality